2018
DOI: 10.1038/s41598-018-23499-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields increase osteogenetic commitment of MSCs via the mTOR pathway in TNF-α mediated inflammatory conditions: an in-vitro study

Abstract: Pulsed electromagnetic fields (PEMFs) have been considered a potential treatment modality for fracture healing, however, the mechanism of their action remains unclear. Mammalian target of rapamycin (mTOR) signaling may affect osteoblast proliferation and differentiation. This study aimed to assess the osteogenic differentiation of mesenchymal stem cells (MSCs) under PEMF stimulation and the potential involvement of mTOR signaling pathway in this process. PEMFs were generated by a novel miniaturized electromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 38 publications
2
34
0
1
Order By: Relevance
“…Previous studies have found that integrin signaling pathway, mTOR signaling pathway, Wnt / β-catenin signaling pathway, Hippo pathway, and others, play important roles in traction osteogenesis. Some studies have found that Smad pathway, mitogen-activated protein kinase (MAPKs) pathway, etc., are also activated to varying degrees in osteotomy osteogenesis [35][36][37][38]. In our study, we found that ECM-receptor interaction, focal adhesion, Hippo signaling pathway-multiple species, PI3K-Akt signaling pathway, Wnt signaling pathway, Hippo signaling pathway, and other pathways show obvious trends of up-regulation in traction osteogenesis, thus indicating that these pathways may indeed be important in distraction osteogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have found that integrin signaling pathway, mTOR signaling pathway, Wnt / β-catenin signaling pathway, Hippo pathway, and others, play important roles in traction osteogenesis. Some studies have found that Smad pathway, mitogen-activated protein kinase (MAPKs) pathway, etc., are also activated to varying degrees in osteotomy osteogenesis [35][36][37][38]. In our study, we found that ECM-receptor interaction, focal adhesion, Hippo signaling pathway-multiple species, PI3K-Akt signaling pathway, Wnt signaling pathway, Hippo signaling pathway, and other pathways show obvious trends of up-regulation in traction osteogenesis, thus indicating that these pathways may indeed be important in distraction osteogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Once isolated, hADSCs were induced to osteogenic differentiation and contextually exposed to HBO, HB or HO daily for 60 min, with the aim to replicate the duration of treatment received by hyperbaric therapy patients [3]. Each treatment was carried out for 21 days, which is generally considered an appropriate time period for in vitro evaluating the osteogenic differentiation properties of hADSCs [30].…”
Section: Discussionmentioning
confidence: 99%
“…In our samples we found a great quantity of ROS and high gene expression levels of mitochondrial genes related to ROS production, confirming the abnormal presences of this marker in the peri-implantitic tissue. Moreover, in recent years researchers highlighted its role as signaling molecules [17][18][19][20] impacting MSC differentiation. Evidence supports the strong relation with impaired skeletal integrity: increased levels of intracellular ROS induce the MSC potential in osteogenic differentiation [21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%